Discalculia y su influencia en el aprendizaje matemático en los estudiantes del cuarto año de educación básica de la Unidad Educativa Pichincha, Provincia de Manabí año 2018 - Mendoza Quiroz, Darwin Alexander (2019)
In these times, the Discalculia is estimated as a teaching problem that makes total mathematics instruction impossible, so it is common to observe in some schools that there are students with low performance in this subject, however, being a cerebral situation , suffers the ability to understand and work with numbers and mathematical concepts. Some children with Discalculia are unable to reason numerical concepts and work hard to learn and memorize numerical data, so they may come to understand what to do in math class, but they do not understand why they do it, in other words, they the logic of the process makes it difficult for them. In this research work the qualitative method was used, through the application of a survey applied to parents and students of the fourth year of basic education of the Educational Unit "Pichincha", to establish the use of methodological strategies in the Mathematics subject and determine the importance of their learning throughout life, being able to verify that although teachers claim to use good strategies, these are not appropriate, and that they also depend on creative resources, to achieve children's motivation.